The occipital place area represents first-person perspective motion information through scenes. (October 2016) - Kamps, Frederik S.; Lall, Vishal; Dilks, Daniel D.
Abstract: Neuroimaging studies have identified multiple scene-selective regions in human cortex, but the precise role each region plays in scene processing is not yet clear. It was recently hypothesized that two regions, the occipital place area (OPA) and the retrosplenial complex (RSC), play a direct role in navigation, while a third region, the parahippocampal place area (PPA), does not. Some evidence suggests a further division of labor even among regions involved in navigation: While RSC is thought to support navigation through the broader environment, OPA may be involved in navigation through the immediately visible environment, although this role for OPA has never been tested. Here we predict that OPA represents first-person perspective motion information through scenes, a critical cue for such "visually-guided navigation", consistent with the hypothesized role for OPA. Response magnitudes were measured in OPA (as well as RSC and PPA) to i) video clips of first-person perspective motion through scenes ("Dynamic Scenes"), and ii) static images taken from these same movies, rearranged such that first-person perspective motion could not be inferred ("Static Scenes"). As predicted, OPA responded significantly more to the Dynamic than Static Scenes, relative to both RSC and PPA. The selective response in OPA to Dynamic Scenes was not due to domain-general motion sensitivity or to low-level information inherited from early visual regions. Taken together, these findings suggest the novel hypothesis that OPA may support visually-guided navigation, insofar as first-person perspective motion information is useful for such navigation, while RSC and PPA support other aspects of navigation and scene recognition.